Pigmented basal cell carcinoma: An uncommon lesion with special emphasis on cytological features (Indian Journal of Case Reports, 2020)
Pigmented basal cell carcinoma (PBCC) is a rare cutaneous neoplasm with only a few cases described in the literature so far. We report a case of PBCC that developed on the right lower eyelid with an elucidation of cytomorphological features of this rare variant of basal cell carcinoma to make a cytopathologist aware of the characteristic cytological features of this tumor. These cytological features of PBBC aid in the identification of these tumors on cytology. We also briefly discuss the possible differential diagnoses.